Neglected Children : Research, Practice and Policy. - Dubowitz, Dr. Howard (SAGE Publications, 1999)
Child neglect is the most common type of child maltreatment. Substantial evidence indicates that the morbidity and mortality associated with neglect are significant, with enormous costs to the children involved and to society. Yet there is no major text focused exclusively on child neglect. Neglected Children presents a comprehensive and critical portrait of the phenomenon of neglect, based on theory, research and clinical practice experience. The editor and the contributing authors present a rich, interdisciplinary conceptualization with a broad view of neglect, moving far beyond the curr.